c.2 - "Jain, Aarushi" (New Delhi, 2011)
This book is a humble attempt in the study of above issues and is based on empirical research conducted by the author. In the book, I have tried to comprehensively discuss the concepts of Rural Development, Corporate Social Responsibility and Public Private Partnership. After a general introduction about the issues in the first chapter, the second chapter discusses the current rural development scenario, the rural development schemes, rural development administration and Panchayati raj institutions and also the new trends and the changing paradigm of harmonized rural development in India. In the third chapter, the concept, evolution, types, components, measurement and benefits of CSR are discussed. The chapter also talks of CSR in the Indian Perspective and certain best practices of CSR in India.
Keywords: Public private partnership